ENTRAPMENT LEADING TO TESTILYING BY POLICE IN NARCOTICS CASES: Penjebakan (Entrapment) Berujung Pada Kesaksian Bohong (Testilying) Oleh Polisi Pada Kasus Narkotika - Arie Ramadhani; Desi Yunita Putri (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The harshness of the war on narcotics ironically did not bring significant improvements to reduce the number of illicit drug trafficking or the level of drug use or abuse. In addition, the war on narcotics also caused law enforcement efforts in narcotics cases to be far from compliance with fair trial norms. The problems raised from this study regarding the factors causing police officers to commit entrapment, Engineering and Deceptive Techniques which ended in giving false testimony (Testilying) in Court in narcotics cases, how the Supreme Court Judge's decision is reviewed from moral principles. The type of research used is pure normative legal research, namely research that focuses on studying secondary legal materials and then analyzed using the logic of legal science. The results of this study are that the three investigative techniques in the form of entrapment, engineering and deceptive techniques are techniques that are not allowed in the Criminal Justice System in Indonesia, because this technique will also end in police testilying. The implementation of this technique occurs due to several factors, including public support for this practice, the high target of arrests by the police in narcotics cases and the performance of the police from the arrest indicator so that the war on drugs becomes the wrong target.